2018
DOI: 10.1093/ehjci/jey050
|View full text |Cite
|
Sign up to set email alerts
|

Exercise cardiac magnetic resonance to differentiate athlete’s heart from structural heart disease

Abstract: Functional cardiac evaluation during exercise is a promising tool in differentiating healthy athletes with borderline LVEF from those with an underlying cardiomyopathy. Excellent exercise capacity does not exclude significant LV damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 34 publications
2
44
0
Order By: Relevance
“…Our finding that 11.6% of EC and 6.7% of SEC present with reduced EF emphasizes the challenge of differentiating physiological and pathological adaptation in this group. Claessen et al 39 have previously demonstrated that a low EF in this population is simply a function of increased cavity volume, which requires a lower contractile force to produce the necessary stroke volume.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Our finding that 11.6% of EC and 6.7% of SEC present with reduced EF emphasizes the challenge of differentiating physiological and pathological adaptation in this group. Claessen et al 39 have previously demonstrated that a low EF in this population is simply a function of increased cavity volume, which requires a lower contractile force to produce the necessary stroke volume.…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, E velocity and E’ velocity were both lower in EC (compared to NA), which indicate lower diastolic function. The most likely explanation for these lower values may be a significantly greater reserve volume and lower resting HR in comparison to both SEC and NA, resulting in a decreased need for enhanced relaxation/suction at rest 39 …”
Section: Discussionmentioning
confidence: 99%
“…In terms of differentiating the athletic heart from cardiomyopathy, when 10 healthy endurance athletes were compared with 9 endurance athletes with subepicardial fibrosis and 5 patients with dilated cardiomyopathy, they demonstrated a significantly greater augmentation of LV ejection fraction (LVEF) during exercise of 14 ± 3%, compared with 4 ± 3% and 5 ± 6% respectively. The endurance athletes with subepicardial fibrosis had similar resting haemodynamics and exercise capacity to the healthy endurance athletes, suggesting that Ex-CMR may be helpful in differentiating healthy endurance athletes from those with fibrosis [63].…”
Section: Athletic Heart Diseasementioning
confidence: 84%
“…Conduction disease such as left bundle branch block or repolarisation abnormalities such as pathological T wave inversions are similarly suggestive of cardiomyopathy. Ventricular arrhythmias, either on ambulatory monitoring or exercise testing as well as functional testing abnormalities including a low peak oxygen consumption (VO 2 ) on cardiopulmonary exercise testing or a failure to increase LVEF by at least 11% on peak exercise imaging [ 61 ] potentially indicate disease. Specific additional imaging parameters including moderate or severe LV systolic impairment, diastolic dysfunction, regional wall motion abnormalities and late gadolinium enhancement on CMR have also been proposed as discriminatory features favouring pathology.…”
Section: Management Of Athletes With Excessive Trabeculationmentioning
confidence: 99%